2013
DOI: 10.1167/iovs.13-11754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cell Surface Markers Glypican-4 and CD200 That Differentiate Human Corneal Endothelium From Stromal Fibroblasts

Abstract: Taken together, the anti-GPC4 and anti-CD200 antibodies can be useful for purification and identification of HCECs in cultures containing stromal fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 29 publications
1
57
2
Order By: Relevance
“…10 To date, no HCEC-specific cell surface markers have been elucidated, although two groups have reported the expression of CD markers. 11,12 The effector cell did not show any sign of surface CD200. Okumura et al 11 have reported that CD340, CD166, and CD98 are elevated in HCECs of nonfibroblastic phenotype, while CD9, CD49e, CD44, and CD73 are the indices of fibroblastic phenotypes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…10 To date, no HCEC-specific cell surface markers have been elucidated, although two groups have reported the expression of CD markers. 11,12 The effector cell did not show any sign of surface CD200. Okumura et al 11 have reported that CD340, CD166, and CD98 are elevated in HCECs of nonfibroblastic phenotype, while CD9, CD49e, CD44, and CD73 are the indices of fibroblastic phenotypes.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, cHCECs are heterogeneous from culture to culture in their morphology and in their surface markers, such as cluster of differentiation (CD) antigens. [10][11][12] Studies, [13][14][15][16][17][18][19][20] either directly or indirectly, and including those from Joyce et al, have shown that heterogeneity is present in HCEC cultures. Of particular and striking interest is the finding by Miyai et al 10 of the presence of frequent chromosomal aneuploidy in cHCECs, thus indicating the presence of heterogeneous subpopulations (SPs) with or without aneuploidy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…n = 4, *p < 0.01, and **p < 0.05. Primary CECs were cultivated using the dual media approach to the third passage and characterized for their expression of known markers indicative of the corneal endothelium such as (B) sodium-potassiumtransporting adenosine triphosphatase (Na and expressed higher levels of corneal endothelium-specific genes ATP1A1, SLC4A11 and COL8A1, as well as reported cellular markers of the corneal endothelium (11,44).…”
Section: Characterization Of Cultivated Human Corneal Endothelial Celmentioning
confidence: 99%
“…In fact, cHCECs are known to be heterogeneous from culture to culture in their morphology and in their surface markers, such as cluster-ofdifferentiation (CD) antigens. [3][4][5] Studies, either directly or indirectly, and including those from Joyce et al, [6][7][8][9][10][11][12][13] have shown that heterogeneity is present in HCEC cultures. Of particular and striking interest is the finding by Miyai et al 3 of the presence of frequent chromosomal aneuploidy in cHCECs, directly indicating the presence of heterogeneous subpopulations (SPs) with or without aneuploidy.…”
mentioning
confidence: 99%